The Relationship Between Pap Smear Screening Adherence and Cervical Cancer Mortality: A Systematic Review - Bangar Parlinggoman Tua; Yahya Nurlianto; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
INTRODUCTION: Cervical cancer remains a leading cause of cancer-related mortality for women globally, with a disproportionate burden concentrated in low- and middle-income countries (LMICs) (World Health Organization, 2024). This significant disparity is largely attributable to inadequate implementation of, and adherence to, preventive screening programs (Bray et al., 2024). This systematic review synthetically evaluates the quantitative association between adherence to Papanicolaou (Pap) smear screening and cervical cancer mortality. METHODS: A systematic review of the literature was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (Page et al., 2021). Major electronic databases (including PubMed, MEDLINE, Embase, and Web of Science) were searched for observational studies (cohort and case-control) that assessed cervical cancer mortality or the incidence of invasive cervical cancer as an outcome of cytology screening history (Peirson et al., 2013). Study quality and risk of bias were assessed using the Newcastle-Ottawa Scale (NOS), the standard, validated tool for non-randomized studies (Wells et al., 2000). RESULTS: A total of 16 high-impact observational studies met the inclusion criteria. The findings are overwhelmingly consistent and statistically significant in demonstrating a profound protective effect. Large-scale cohort studies demonstrate that women adhering to screening have a substantially lower risk of mortality; one major study found a 70% reduction in cervical cancer mortality (Hazard Ratio: 0.30; 95% Confidence Interval [CI]: 0.12–0.74) (Makino et al., 2006). Case-control studies report exceptionally strong protective effects, with odds ratios (OR) for mortality as low as 0.08 (95% CI: 0.07–0.09) (Landy et al., 2016) and 0.34 (95% CI: 0.14–0.49) (Lönnberg et al., 2013). Furthermore, a meta-analysis of case-control studies on invasive cancer (the precursor to mortality) found a pooled protective effect (OR: 0.35; 95% CI: 0.30–0.41), signifying an approximate 65% reduction in risk (Peirson et al., 2013). DISCUSSION: The evidence irrefutably confirms a significant inverse relationship between screening adherence and mortality. The epidemiological findings demonstrate that the public health failure is not one of diagnostic efficacy but of implementation. This discussion synthesizes the quantitative efficacy of screening with the major documented barriers—economic, psychosocial, cultural, and provider-level—that suppress adherence rates and perpetuate this preventable mortality (Akin-Odanye et al., 2024). CONCLUSION: Adherence to Pap smear screening is a critical, primary determinant in the prevention of cervical cancer mortality. Public health strategies must shift from proving efficacy to aggressively dismantling the known structural and psychosocial barriers to adherence to achieve global elimination targets.